EFL Students' Dependence on ChatGPT and Its Impact on the English Learning Process - Awalda Zulfa Heryani; Musdizal Musdizal (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2025)
This study aims to examine EFL Students’ dependence on ChatGPT and its impact on their English learning process. The study focuses on second-semester students of the English Education program at an Islamic higher education institution in Jambi, Indonesia. A qualitative descriptive approach was employed, using semi-structured interviews with five participants. The data were analysed thematically to identify students’ experiences and perceptions. The findings indicated that ChatGPT provides positive benefits, including improvements in vocabulary, grammar, and writing skills, as well as rapid feedback accompanied by clear explanations. However, the study also reveals several negative impacts of ChatGPT use, such as decreased critical thinking skills, excessive dependence on AI-generated content, and reduced intrinsic motivation for independent learning. Therefore, this study emphasises that although ChatGPT serves as a supportive tool in English language learning, its use needs to be carefully managed to ensure responsible and effective application. The findings offer insights for educators in integrating ChatGPT by balancing AI technological support with students’ own learning efforts, so that learners remain active and independent in the English learning processThis study aims to examine EFL Students’ dependence on ChatGPT and its impact on their English learning process. The study focuses on second-semester students of the English Education program at an Islamic higher education institution in Jambi, Indonesia. A qualitative descriptive approach was employed, using semi-structured interviews with five participants. The data were analysed thematically to identify students’ experiences and perceptions. The findings indicated that ChatGPT provides positive benefits, including improvements in vocabulary, grammar, and writing skills, as well as rapid feedback accompanied by clear explanations. However, the study also reveals several negative impacts of ChatGPT use, such as decreased critical thinking skills, excessive dependence on AI-generated content, and reduced intrinsic motivation for independent learning. Therefore, this study emphasises that although ChatGPT serves as a supportive tool in English language learning, its use needs to be carefully managed to ensure responsible and effective application. The findings offer insights for educators in integrating ChatGPT by balancing AI technological support with students’ own learning efforts, so that learners remain active and independent in the English learning process